Kekuatan Hukum Jual Beli Online Baju Melalui Transaksi Blackberry Messenger - Rokhimaturrozaq, Wildan Aulia, Kelik Wardiono,. M.Hum, Inayah, SH,. M.H. (2016)
ABSTRACT At this time many Severability Sell Online Buy Clothes Through Transactions Blackberry Messenger. If not careful in choosing a product or service that consumers want to be the only object of exploitation and entrepreneurs who are not responsible. For that we need the legal protection of consumers in the sale and purchase of an item displayed in the internet abusive situation connected by Act 8 of 1999 on Consumer Protection. Abuse situation occurs because there are two elements, namely a loss for one party and abuse by the other party a chance. Legal protection of consumers is regulated by Law No. 8 of 1999 on the rotection Konsumen.Undang this law is expected to ensure legal certainty for consumers in e-commerce transactions. Based on the discussion of the results of this study concluded that the consumer protection Act No. 8 of 1999 has not been able to protect consumers in e-commerce transactions because of limited understanding of businesses that specialized only in the territory of the Republic of Indonesia.Keywords: Laws, Consumer Protection, Agreements, Buying and selling, online transactions via blackberry